Zooming In On The Money Shot: An Exploratory Quantitative Analysis of Pornographic Film Actors - O'Neal, Erin (2016)
Sex work is one of the rare elements of our society that is both accepted and stigmatized. Ironically enough, it is stigmatized without being studied in depth. The truth is we know very little about sex work and even less about pornography—the most legal of genres. While researchers have spent a great deal of time determining the effects that pornography has on viewers, particularly juvenile viewers, little research has been done on the men and women who make pornography. A 43 question survey was created and disseminated to those in the pornographic film industry, both amateur and professional, resulting in 210 respondents from all walks of life. The results of the inquiry show that social scientists know relatively little about working in pornography, having a profound impact on the current discussion and future research. Additionally, this investigation presents a new and creative method for surveying hard to reach, hidden, or sensitive subject populations that will aid in aspects of future research on sex work and other stigmatized behaviors